A dual-interface load transfer model for precast concrete-cored cemented soil piles considering progressive damage - Haian Liang; Yating Zhu; Lanlan Xu; Hongyan Wu; Junpeng Zhang; Bin Xu; Kaiwei Cao (PLoS ONE, 2026)
Precast concrete-cored cemented soil piles (PCCS) are widely used to improve the bearing capacity of soft ground. However, existing design models usually assume perfect bonding between the concrete core and cemented soil shell, ignoring progressive interface damage under external loads, which leads to inaccuracies in bearing capacity predictions. This study proposes a dual-interface load transfer model that explicitly simulates progressive interface damage. Its innovation lies in the coupling of an exponential damage constitutive model for the inner concrete–cemented soil interface calibrated by direct shear tests with an elastoplastic model for the outer cemented soil–surrounding soil interface, along with a convergent iterative algorithm for solving the governing equations. Verified by field measurements of the test pile in Jiangxi Province, China, the model shows strong agreement with measured data R 2 = 0 . 9746 . Quantitative analysis shows that the concrete core bears more than 90% of the pile-head load, and the cemented soil shows a distinctive C-shaped axial force distribution along the pile shaft. The model captures the coupled evolution of load sharing and skin friction at both interfaces, providing theoretical support for the refined design and safety assessment of PCCS foundations.